Model of care for low birth weight newborns by levels according to risk factors (Colombia Medica, 1994)
We present the model of attention for low birth weight neonates according to risk factors, which is operating in Cali, Colombia. The model has the facilities of one level III hospital, one level II hospital, and 6 level I centers. We show the data obtained from October to December 1991. During this time48% of admitted neonates were low birth weight newborns, 85% of them were admitted to the system through level III. From this level, they were transferred to lower-level facilities, and finally, they were discharged home. The average time being managed ali along the system was 19 days. Complex pathology received treatment mainly at levels III and II. Global mortality was 28%, and it opened usually at level III (89%). We conclude the management of low birthweight neonates can be optimized according to the risk factors at birth, admitting in level III the high-risk newborn and sending to lower complexity level the uncomplicated newborns and babíes who are showing improvements This policy does not increase the rísk of complícatíons or mortalíty, but promotes early contact with the mother and decreases expenses in the system.